How do risks and benefits affect user’ privacy decisions? An event-related potential study on privacy calculus process - Fu, Jialin; Zhang, Jiaming; Li, Xihang (Frontiers in Psychology, 2023)
Privacy paradox refers to the phenomenon that users disclose their privacy to exchange for information or services provided by enterprises despite their concerns about privacy security. Although previous studies have done extensive analysis of the factors that influence privacy decisions, the results based on questionnaires and interviews may include biased and inaccurate answers and have limitations in explaining how these factors affect users’ privacy decision. This study investigates the process how risks and benefits affect privacy decision-making process through event-related potential experiment. The findings show that users subconsciously categorize personalized services based on benefit; Privacy calculus affects privacy decision by influencing the allocation of cognitive resources for personalized service, and the scarcity of cognitive resources increases the degree of privacy disclosure; Emotional change in privacy decision is the result of many factors, not the result of privacy risk alone. This study provides a new perspective to explain the process of privacy decision-making, and a new approach to investigate the privacy paradox.